2013
DOI: 10.1002/acp.2937
|View full text |Cite
|
Sign up to set email alerts
|

Gestures in Instructional Animations: A Helping Hand to Understanding Non‐human Movements?

Abstract: Recent research on dynamic visualizations suggests that these visualizations are effective for learning human movements such as knot tying or paper folding. Using embodied theories of cognition, this study investigated whether learning non-human movements from a dynamic visualization can also be enhanced by grounding these movements in the learner's motor system. University students viewed an animation on lightning formation, and followed the animation's movements with gestures, saw an on-screen human hand fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 37 publications
4
35
2
Order By: Relevance
“…Furthermore, all age groups had performed better and experienced less mental effort on the simple versus the complex problems, which indicates that our measures were sensitive to variations in complexity and cognitive load. Although our design has proven to be valid in manipulating task complexity and sensitive to detect an effect of age, the results showed almost no effect of gestures, which is not in line with previous studies that did show a positive effect of observing gestures on learning (De Koning & Tabbers, 2013) and problem solving (Lozano & Tversky, 2006). This difference might be caused by the type of task used; De Koning and Tabbers (2013) did not look into problem solving, and Lozano and Tversky (2006) used a more concrete type of problem solving (assembly of a simple object).…”
Section: Discussioncontrasting
confidence: 85%
“…Furthermore, all age groups had performed better and experienced less mental effort on the simple versus the complex problems, which indicates that our measures were sensitive to variations in complexity and cognitive load. Although our design has proven to be valid in manipulating task complexity and sensitive to detect an effect of age, the results showed almost no effect of gestures, which is not in line with previous studies that did show a positive effect of observing gestures on learning (De Koning & Tabbers, 2013) and problem solving (Lozano & Tversky, 2006). This difference might be caused by the type of task used; De Koning and Tabbers (2013) did not look into problem solving, and Lozano and Tversky (2006) used a more concrete type of problem solving (assembly of a simple object).…”
Section: Discussioncontrasting
confidence: 85%
“…For example, De Koning and Tabbers (2013) compared visual signaling via an arrow and via a picture of a pointing hand and found learning benefits associated with viewing the pointing hand. Similarly, Johnson and colleagues (De Koning & Tabbers, 2013) found that students with low prior knowledge benefitted more from agent gesture than from an arrow.…”
Section: Discussionmentioning
confidence: 99%
“…In a large field experiment, Piasta et al (2012) found that the use of preschool teachers' print references enhanced children's early literacy skills, including reading, spelling, and comprehension, 2 years after the intervention's conclusion. Other recent multimedia-based studies with adult participants have found improved learning when attention-capturing signals such as animated cursors were replaced with images of the human hand pointing (e.g., Atkinson et al 2009;Castro-Alonso et al 2014;de Koning and Tabbers 2013), or an animated avatar pointing to specific aspects of on-screen information (Mayer and DaPra 2012;Moreno et al 2010).…”
Section: Pointing and Tracing To Support Learning Of Biologically Secmentioning
confidence: 99%